2019
DOI: 10.3389/fpls.2019.00318
|View full text |Cite
|
Sign up to set email alerts
|

Luxury Vegetative Nitrogen Uptake in Maize Buffers Grain Yield Under Post-silking Water and Nitrogen Stress: A Mechanistic Understanding

Abstract: During vegetative growth maize can accumulate luxury nitrogen (N) in excess of what is required for biomass accumulation. When post-silking N uptake is restricted, this luxury N may mitigate N stress by acting as an N reserve that buffers grain yield and maintains plant function. The objective of this study was to determine if and how luxury accumulation of N prior to silking can buffer yield against post-silking N and/or water stress in maize. In a greenhouse experiment, maize was grown in high (N … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 65 publications
0
22
1
Order By: Relevance
“…Nitrogen is particularly essential for corn grain development. Its uptake in roots as well as its relocation from leaves impact directly on grain quality [146,147]. The stay-green phenotype has been studied in corn for several decades, although the molecular mechanism remains unclear [148,149].…”
Section: Main Tfs Associated With Leaf Senescence In Cropsmentioning
confidence: 99%
“…Nitrogen is particularly essential for corn grain development. Its uptake in roots as well as its relocation from leaves impact directly on grain quality [146,147]. The stay-green phenotype has been studied in corn for several decades, although the molecular mechanism remains unclear [148,149].…”
Section: Main Tfs Associated With Leaf Senescence In Cropsmentioning
confidence: 99%
“…In general, FR often results in a maize grain yield increase in response to increasing N rates if no water stress occurs [26]. However, unlimited N doses are recognized to cause crop luxury consumption, which is a process to avoid in sustainable farming [5,49]. Generally, in the first year, the mean maize yield was consistent with that observed by the farmer in the previous years.…”
Section: Discussionmentioning
confidence: 66%
“…Fertilization is one of the most relevant targets of this new approach [4]. Indeed, adjusting the N rate to the measured crop requirement increases crop N use efficiency [5,6] and reduces environmental risks [7][8][9]. Delgado et al 2005 [10] reported that applying N using VR can reduce NO 3 leaching losses by 25%.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike in the case of field grass, a deficit of 57 kg N ha −1 is calculated when cup plant was grown beforehand. However, it must be taken into account that maize shows luxury N consumption where there is a surplus of available N (Herrmann & Taube, 2005; Nasielski et al, 2019). In fact, the maize biomass N concentration of 13.7 g N kg −1 DM following cup plant clearly exceeded the critical N concentration of 10.5 g N kg −1 DM which according to Herrmann and Taube (2005) is necessary for attaining maximum biomass yields in northern Germany.…”
Section: Discussionmentioning
confidence: 99%